2008
DOI: 10.1002/cbic.200800361
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Transfer Difference (STD) NMR Spectroscopy Characterization of Dual Binding Mode of a Mannose Disaccharide to DC‐SIGN

Abstract: Concurrent multiple binding modes of a single ligand can be detected and quantified by saturation transfer difference (STD) NMR spectroscopy. Analysis of experimental and predicted STD initial growing rates has allowed us to determine the precise orientation of Man α(1→2)Man in the minor complex with the carbohydrate recognition domain of DC‐SIGN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…3A [see SI Appendix for NMR assignment (SI Appendix, Table S1)]. To precisely map ligand epitopes in close contact with the protein, we acquired STD build up curves by collecting spectra at different saturation times (25)(26)(27)(28) and fitting experimental data with the monoexponential equation: STD = STD max [1 -exp (−k sat t)] (see Materials and Methods, NMR Spectroscopic Analysis for complete details). This method avoids artifacts in the epitope definition, which are consequences of differences in ability to accumulate saturation in the free state, allowing to obtain the real STD effect of each proton, independently of T1 bias, and to prevent any misinterpretation of STD enhancements.…”
Section: Std Nmr Epitope Mapping Of Chitin Oligosaccharides In the Prmentioning
confidence: 99%
“…3A [see SI Appendix for NMR assignment (SI Appendix, Table S1)]. To precisely map ligand epitopes in close contact with the protein, we acquired STD build up curves by collecting spectra at different saturation times (25)(26)(27)(28) and fitting experimental data with the monoexponential equation: STD = STD max [1 -exp (−k sat t)] (see Materials and Methods, NMR Spectroscopic Analysis for complete details). This method avoids artifacts in the epitope definition, which are consequences of differences in ability to accumulate saturation in the free state, allowing to obtain the real STD effect of each proton, independently of T1 bias, and to prevent any misinterpretation of STD enhancements.…”
Section: Std Nmr Epitope Mapping Of Chitin Oligosaccharides In the Prmentioning
confidence: 99%
“…[12] We have shown that such multimodal systems can be quantitatively treated by an appropriate analysis of STD NMR experiments based on STD initial growth rates. Thus, the experimental system can be deconvoluted as a simple sum of the contributions from each mode.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the experimental system can be deconvoluted as a simple sum of the contributions from each mode. [12] This approach is justified by considering the effects of fast ligand rebinding during the receptor saturation in the STD experiment. If there is a certain probability that a given ligand molecule reenters into the binding site after a preceding binding event (and this rebinding is fast enough related to the relaxation properties), then the ligand spin populations would be partially perturbed due to the previous transfer step, and hence, its capacity to receive more transfer of saturation from the receptor will be different than that from a fresh ligand molecule.…”
Section: Introductionmentioning
confidence: 99%
“…6). We also calculated the STD values at a very low saturation time (100 ms) to assess whether consideration of the initial STD build-up would lead to more reliable predictions [8,9]. The overall profile of this GEM, with low values for all protons except the C6 protons, did fit well with the transferred magnetisation rates, but the ordering of the other protons are again rather poor (Fig.…”
Section: Case A: Jacalinmentioning
confidence: 99%
“…Although the influences are smaller, the observed STD values are still affected by such relaxation processes combined with the exchange kinetics. A more precise and recently used method is to fit the build-up of the STD to an exponential curve and estimate the initial slope [8,9]. This approach is usually done with short saturation times ($0.3 s), meaning the measured STDs are often intrinsically weak and thus more difficult to quantify, so this approach also imposes undesirable experimental consequences and may be time intensive.…”
Section: Theoretical Basismentioning
confidence: 99%